CURRENT STATUS OF POPULATION AND ECOLOGICAL PECULIARITIES OF THE EURASIAN BEAVER CASTOR FIBER L. IN ROSTOV REGION - Valeriy V. Stakheev; Vlalimir Yu. Shmatko; Nikita V. Panasyuk; Aleksey V. Kleshchenkov (Юг России: экология, развитие, 2018)
Aim. Are considered the issues of distribution, the current state, and some ecological peculiarities of the Eurasian beaver Castor fiber in the Rostov region in the south of their range. Methods. The materials presented in the study were collected predominantly in the spring-summer months, based on the information from hunting specialists. Was used the method of counting the number of inhabited settlements. Was also considered the confinement of the animal to certain stations, as well as to the width of the river bed. Results. Over the past two decades, this species has significantly expanded its distribution in the region and settled along the right bank of the Don River up to its mouth. Currently, the number of beavers in the Rostov region is estimated at over 2300 individuals. At the same time, the overwhelming majority of them inhabit the administrative regions located in the north of the region and are more connected with the rivers of Seversky Donets, Kalitva, Chir, the middle course of the Don River. Conclusion. In the Rostov region, the beaver demonstrates the main elements of occupying the territories, which is expressed in the prevalence of construction of burrows over the construction of huts, as well as the absence of dams and canals. In the near future, there is a probable increase in the density of the population of the beaver in the lower reaches of the Don, as well as the colonization of the rivers of the northern part of the Azov Sea.